Implementing Psychological First-Aid Training for Medical Reserve Corps Volunteers. (27th February 2014) - Chandra, Anita; Kim, Jee; Pieters, Huibrie C.; Tang, Jennifer; McCreary, Michael; Schreiber, Merritt; Wells, Kenneth
Abstract Objective We assessed the feasibility and impact on knowledge, attitudes, and reported practices of psychological first-aid (PFA) training in a sample of Medical Reserve Corps (MRC) members. Data have been limited on the uptake of PFA training in surge responders (eg, MRC) who are critical to community response. Methods Our mixed-methods approach involved self-administered pre- and post-training surveys and within-training focus group discussions of 76 MRC members attending a PFA training and train-the-trainer workshop. Listen, protect, connect (a PFA model for lay persons) focuses on listening and understanding both verbal and nonverbal cues; protecting the individual by determining realistic ways to help while providing reassurance; and connecting the individual with resources in the community. Results From pre- to post-training, perceived confidence and capability in using PFA after an emergency or disaster increased from 71% to 90% (P < .01), but no significant increase was found in PFA-related knowledge. Qualitative analyses suggest that knowledge and intentions to use PFA increased with training. Brief training was feasible, and while results were modest, the PFA training resulted in greater reported confidence and perceived capability in addressing psychological distress of persons affected by public health threats. Conclusion PFA training is a promising approach to improve surge responder confidence and competency in addressing postdisaster needs. (Disaster Med Public Health Preparedness. 2014;0:1-6)